The Criticism of Net Present Value and Equivalent Annual Cost - KOGAN, Anton (Journal of Advanced Research in Law and Economics; Vol 5 No 1 (2014): JARLE, Volume V, Issue 1(9), Summer 2014, 2017)
The article deals with the indicators used when making investment decisions in situations when it is necessary to invest different amounts of money in alternative real assets for different periods of time. The author suggests two new indicators: ‘the indicator of the speed of specific increment in value’ (IS) and ‘conditional bank deposit’ (CBD). The first indicator is used to choose the best investments that bring some profit. The second indicator is used to choose the best investments that do not directly bring profit, but are required for the operation of the company.